2020
DOI: 10.1101/2020.02.28.969725
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In Arabidopsis, low blue light enhances phototropism by releasing cryptochrome 1-mediated inhibition ofPIF4expression

Abstract: Shade-avoiding plants including Arabidopsis thaliana display a number of growth responses elicited by shade cues including elongation of stem-like structures and repositioning of leaves. Shade also promotes phototropism of de-etiolated seedlings through repression of phytochrome B (phyB) presumably to enhance capture of unfiltered sunlight. Light cues indicative of shade include a reduction in the blue and red portions of the solar spectrum and a low red to far-red ratio. Here we show that in Arabidopsis seedl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…Previous work had shown that LRFR can promote phototropism in artificial lighting conditions (Goyal et al, 2016), where etiolated seedlings are exposed to a unidirectional source of blue light. However, with a more natural lighting regime, Boccaccini et al (2020) found that LRFR was not sufficient. Only a combination of LBL and LRFR resulted in increased phototropism toward a blue light source within the white growth light (WL; Fig.…”
Section: True Blue: How Cry1 Inhibits Phototropism In Green Seedlingsmentioning
confidence: 95%
See 4 more Smart Citations
“…Previous work had shown that LRFR can promote phototropism in artificial lighting conditions (Goyal et al, 2016), where etiolated seedlings are exposed to a unidirectional source of blue light. However, with a more natural lighting regime, Boccaccini et al (2020) found that LRFR was not sufficient. Only a combination of LBL and LRFR resulted in increased phototropism toward a blue light source within the white growth light (WL; Fig.…”
Section: True Blue: How Cry1 Inhibits Phototropism In Green Seedlingsmentioning
confidence: 95%
“…However, plants have another set of blue light photoreceptors, the cryptochromes. Boccaccini et al (2020) discovered that the cry1 mutant has an increased phototropism response in WL/LBL, without a further increase in bending in the LBL/LBL condition, compared with the wild type, which only had a strong response with the LBL pretreatment (LBL/LBL; Fig. 1C).…”
Section: True Blue: How Cry1 Inhibits Phototropism In Green Seedlingsmentioning
confidence: 99%
See 3 more Smart Citations